The influence of Product Quality and Innovation of Huawei Smartphone Products has towards its brand strength and its role in creating committed Consumers - Lay, Kevin (Jurnal Manajemen Update, 2019)
Huawei is one of the world’s largest smartphone manufacturer and China’s oldest and most established brand, in recent years, with the rapid development of the internet and the need of Smartphones, with its large population, Indonesia became the target of Smartphone brands, including Huawei. Although being less popular among its other Chinese brothers in Indonesia, Huawei is gaining a foothold among Smartphone users in the country, especially when Huawei is the only Chinese brand who is in direct competition with the likes of Samsung and Apple. The purpose of this research is to analyze how Huawei Brand Strength is affected by its smartphones Quality and Innovation and how having a strong brand help Huawei in developing consumer’s commitment to the brand. This research is a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. The questionnaire is distributed to 100 sample who fulfill the requirements. The samples of this research are consumers in Pontianak who are above 17 years old who are using Huawei smartphones or have at least used a Huawei smartphone products in the past. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypothesis of the research is H1: There is a significant relationship between product quality and brand strength, H2: There is a significant relationship between innovation and brand strength, H3: There is a significant relationship between brand strength and consumer’s commitment. The result of this research is H1, H2 and H3 are accepted but H2 has the weakest relationship among all variables.Keywords: Huawei, Smartphones, Product Quality, Product Innovation, Brand Strength, Consumer’s Commitment.